The neural correlation of emotion recognition ability and depressive symptoms–evidence from the HCP database - Yuan, Ze; Lin, Xiao; Li, Peng; Gao, Yu-Jun; Yuan, Kai; Yan, Wei; Zhang, Yu-Xin; Liu, Lin; Zhu, Xi-Mei; Zhang, Yi-Jing; Bao, Yan-Ping; Chang, Su-Hua; et al. (Frontiers in Psychiatry, 2023)
Introduction Negative bias of emotional face is the core feature of depression, but its underlying neurobiological mechanism is still unclear. The neuroimaging findings of negative emotional recognition and depressive symptoms are inconsistent. Methods The neural association between depressive symptoms and negative emotional bias were analyzed by measuring the associations between resting state functional connectivity (FC), brain structures, negative emotional bias, and depressive problems. Then, we performed a mediation analysis to assess the potential overlapping neuroimaging mechanisms. Results We found a negative correlation between depressive symptoms and emotional recognition. Secondly, the structure and function of the inferior and lateral orbitofrontal gyrus are related to depressive symptoms and emotional recognition. Thirdly, the thickness of the inferior orbitofrontal cortex and the FC between the inferior orbitofrontal gyrus and fusiform gyrus, precuneate and cingulate gyrus mediated and even predicted the interaction between emotion recognition and depressive symptoms. Finally, in response to a negative stimulus, the activation of the frontal pole and precuneus lobe associated with the inferior orbitofrontal gyrus was higher in participants with depressive symptoms. Conclusion The core brain regions centered on the inferior orbitofrontal cortex such as middle temporal gyrus, precuneus lobe, frontal pole, insula and cingulate gyrus are the potential neuroimaging basis for the interaction between depressive symptoms and emotional recognition.